Utilization of Classroom Reading Corners to Succeed the School Literacy Movement at Malang City, Indonesia - Sumarni, Sumarni; Agus Praseyoningsih, Luluk Sri; Iqbal, Khurshed (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
Literacy at the elementary school level plays a crucial role in building language skills, understanding texts, and critical thinking. Class reading corners are an effective means of increasing student literacy. This research explains student literacy problems and the use of classroom reading corners to make the School Literacy Movement or Gerakan Literasi Sekolah (GLS) at SDN Lesanpuro 2 Malang City a success. The research approach uses descriptive qualitative with a case study type. The subjects in this research were teaching staff and students in grades IV–VI for the 2022/2023 academic year. Observation, interviews, and documentation were carried out in data collection. The research results show that teachers are important in utilizing the classroom reading corner. Utilizing a classroom reading corner is very effective in making the school literacy movement successful if the arrangement is interesting, the activities are varied, and the circulation of reading materials is carried out continuously. Literacy-based learning using the reading corner at SDN Lesanpuro 2 Malang City is carried out through several processes, namely (1) Planning, (2) Exploration, (3) Fairy Tale Show or Reading Together, (4) Book Discussion, (5) Literacy Competition. Continuous use of classroom reading corners can strengthen literacy culture in schools. This is reflected through an increase in the number of students actively visiting the reading corner and an increase in student academic achievement.